Association of the Plasma Long Non-coding RNA MEG3 With Parkinson's Disease - Quan, Yi; Wang, Jia; Wang, Shuo; Zhao, Jizong (Frontiers in Neurology, 2020)
Objective To investigate the expression level (MEG3) of the long non-coding RNA (lncRNAs) in the plasma of Parkinson's disease (PD) patients and its relationship with the disease. Methods 30 PD patients (PD group) who treated at Xuanwu Hospital between January 2017 and December 2019 were selected as the research objects and 30 healthy subjects were enrolled in the study during the same period as the control group. MMSE and MoCA were used to evaluate cognitive function, NMSS was used to evaluate severity of non-motor symptoms. The relative expression of lncRNAs MEG3 in plasma was measured by PCR, and the levels of neuron-specific enolase (NSE), nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) in plasma were measured by ELISA, and the relationship with these all indexes was analyzed . Results The NMSS score of PD group was significantly higher than control group, while the MMSE and MOCA scores were significantly lower than control group (P < 0.05); The relative expression of lncRNAs MEG3, NGF and BDNF levels of PD group were significantly lower than control group, and NSE level was significantly higher than control group (P < 0.05); The H-Y grade and NMSS score in PD group were negatively correlated with the relative expression of lncRNAs MEG3, the levels of NGF and BDNF (P < 0.05), and positively correlated with NSE (P < 0.05); The MMSE and MOCA scores in PD group were positively correlated with the relative expression of lncRNAs MEG3, NGF, BDNF levels (P < 0.05), and negatively correlated with NSE (P < 0.05); The relative expression of lncRNAs MEG3 in PD group was positively correlated with NGF, BDNF levels (P < 0.05), and negatively correlated with NSE (P < 0.05). Conclusion The expression of lncRNAs MEG3 in the plasma of PD patients was downregulated compared to that of control subjects, and its expression level was closely related to the aggravation of non-motor symptoms, cognitive decline, and PD grade. These associations may reflect the synergism of the increase of NSE and decrease of NGF and BDNF levels, highlighting plasma lncRNA MEG3 as a new candidate biomarker of PD.